Sequential adaptation to modality incompatibility - Wirth, Robert; Tonn, Solveig; Schaaf, Moritz; Koch, Iring; Kunde, Wilfried (Journal of experimental psychology. Human perception and performance, 2023)
Modality-compatible stimulus-response mappings (e.g., responding vocally to an auditory stimulus and manually to a visual stimulus) are often easier to perform than modality-incompatible sets (reversed modality mappings). Here, we investigate sequential, trial-to-trial, modulations of modality compatibility effects. By reanalyzing a previous experiment and conducting two specifically tailored, new experiments, we demonstrate robust within-task sequential modulations. Furthermore, we test for between-task adaptations by intermixing the modality switching task with a Simon task. Results show reliable sequential adaptations within the modality switching task, but no transfer of adaptation between tasks in either direction. We discuss how a combination of prominent theoretical accounts such as conflict adaptation and episodic binding can serve as the cognitive underpinnings of the observed sequential adaptations. (PsycInfo Database Record (c) 2023 APA, all rights reserved).